From fad to FAD: A theoretical formulation and proposed name change for "drunkorexia" to food and alcohol disturbance (FAD). Issue 8 (26th July 2018) - Choquette, Emily M.; Rancourt, Diana; Kevin Thompson, J.
Abstract: "Drunkorexia" is a term that has been used to describe behaviors such as restricting food intake in anticipation of alcohol consumption to offset total caloric intake, and/or to enhance the intoxicating effect of alcohol consumption. Scattered studies over the past few years have indicated the potential problematic nature of the intersection of these behaviors, yet there remain significant gaps in the operationalization of the construct, limiting research progress. In this article, we articulate limitations of the current research, including problems with the definition of the construct and a lack of theoretical guidance. We suggest a broader and more accurate phrase to guide future work with this phenomenon: Food and alcohol disturbance (FAD). Additionally, we suggest adapting Fairburn's transdiagnostic theoretical model for FAD. It is hoped these changes might provide a roadmap for future work in this area on risk factors and adaptations of current preventive and treatment approaches to focus on this emerging form of eating disturbance.